Rewitalizacja a partycypacja. Przełamywanie barier mentalnych = Revitalization and participation. Breaking mental barriers - Leszkowicz-Baczyński, Jerzy; Michalski, Zbigniew (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article addresses the problem of revitalization from the perspective of participation. The authors draw attention to the most important obstacles that appear in the process of participatory revitalization. The activities undertaken as part of the revitalization process are frequently vitiated by misunderstanding of the purpose and nature of revitalization. This situation creates problems and barriers resulting in reduced efficiency of the process. The main goal of the article is to indicate and analyze the conditions under which these problems arise and to outline ways to overcome these barriers, especially mental barriers.
Keywords: rewitalizacja społeczna; partycypacja obywatelska; partycypacja wyprzedzająca; bariery mentalne; bottom up; social revitalization; civic participation; anticipatory participation; mental barriers